Implementasi Algoritma Weighted Product (WP) Dengan Model Fuzzy Multi Attribute Decission Making (FMADM) Dalam Penilaian Kinerja Karyawan - Kiki Apni Puspita Sari; Eka Irawan; Fitri Rizky (LPPM STIKOM Tunas Bangsa, 2020)
Employee performance appraisal is a work evaluation activity that is used to determine the quality which will be used for the achievement of each individual employee. The purpose of this research is to appraise employee performance, especially for the security guard. In this study the authors used the Decision Support System technique using the Fuzzy Multi Attribute Decision Making algorithm, namely Weighted Product. The source of the research data used was to provide an assessment form to Krani Papam. In the employee performance appraisal, researchers used 5 assessment criteria, including: Attendance (C1), Responsibility (C2), Commitment (C3), Cooperation (C4), and Motivation (C5). In this study, the alternative used as a sample is employees in the security section (security guard). From the results of manual calculations and system testing, the highest value is 0.0286. It is expected that the results of this study can provide input to the office, especially the security section (security guard) in selecting employee performance so that the assessment is carried out objectively.